ECONOMIC AND SOCIAL NEED FOR STATE SUPPORT - L.M. Sembiyeva,; A.O. Zhagyparova,; Zh. U. Tulegenova,; R.B. Seitova, (Academic Journal of Physical and Chemical Sciences, 2019)
This article aims to identify the positive and negative aspects of state support for small and medium-sized businesses. The authors also reviewed the global experience of SME support. The contribution of the SME sector to GDP in most developed countries ranges from 50% to 60%. In Kazakhstan, SMEs in 2018 provide only 21% of GDP. This is a low value, requiring significant adjustments. In the course of the work, an analysis of the Government’s financing of government programs was conducted, since government programs for financing the economy are highly efficient.